Analysis of Recruitment and Selection Processes in the "Solo Dreaming Community" - Astri Sabrina Anggraini; Rizki Nurhidayah; Salwa Salsabila; Heldy Ramadhan Putra P (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2023)
Recruitment and selection are ways to find and get the ideal member or employee with a set number of quotas. Recruitment and selection are a series of processes used by companies or organizations in search of superior human resources with the required qualifications and standards. The purpose of this research is to learn about the recruitment and selection processes in the Solo Dreamers community, as well as the qualifications and standards of the Solo Dreamers community. The research is qualitative and descriptive, with a qualitative approach through interviews and observations. The results reveal that the recruiting and selection process has been well designed by the Solo Dreamer community in accordance with the needs and expectations of the community. The recruitment process is conducted using open methods and delivered through social media platforms. Selection process in the community of Solo Dreamer, i.e., (1) administrative selection, (2) interview selection, (3) probation or internship (kondisional). Nepotism is an interesting topic when discussing recruitment and selection in an organization or company. In this study, it is revealed that nepotism is forbidden and should be avoided in order to obtain ideal and quality human resources. Selection by looking at social media candidates is one of the most influential qualification assessments in the recruitment and selection process in the Solo Dream Community.